Analysis on the Influence Factors of Bulk Temperature of the Meshing Gear of a Nutation Drive with a Double Circular-arc Spiral Bevel Gear - Chen Ying; Yao Ligang; Wang Xingsheng; Zhang Dawei; Wang Xueying (Jixie chuandong)
The meshing temperature affects the fatigue, vibration, noise and other behaviors in the nutation transmission process of the double circular-arc spiral bevel gear, which cannot be ignored in the life prediction and mechanical response of the double circular-arc spiral bevel gear. In order to reveal the temperature field distribution law of the nutation drive of the double circular-arc spiral bevel gear, the meshing area is obtained by tooth contact analysis of the double circular-arc spiral bevel gear, the thermal load of the gear is obtained by combining tribology and heat transfer, the finite element numerical model of the temperature of the double circular-arc spiral bevel gear is established, and the influence law and reasons of the relevant influencing factors on the bevel gear temperature are analyzed by using the control variable method. The results show that the gear temperature decreases with the increase of modulus, increases with the increase of the spiral angle, and decreases first and then increases with the increase of the nutation angle; the influence of the lubricating oil temperature on the bulk temperature is linear. The research provides reference for reducing the risk of gear failure at high temperatures.